2015
DOI: 10.2903/j.efsa.2015.4290
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety of the extension of use of thaumatin (E 957)

Abstract: Following a request from the European Commission, an exposure assessment was carried out based on the maximum permitted levels (MPLs) authorised in Annex II of Regulation (EC) No 1333/2008 for thaumatin (E 957) and the proposed increase in its use level in flavoured drinks and proposed extension of use in several food categories at the levels proposed by the applicant. The safety of thaumatin as a food additive was previously evaluated by the EU Scientific Committee on Food (SCF) in 1984 and 1988 and by the Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 3 publications
(2 reference statements)
0
18
0
4
Order By: Relevance
“…A further seven studies were identified from authoritative sources [70,71,72,73,74,75,76]. These data examined exposure by various EU population groups to all seven sweeteners of interest.…”
Section: Methodology and Trends In Intakementioning
confidence: 99%
See 3 more Smart Citations
“…A further seven studies were identified from authoritative sources [70,71,72,73,74,75,76]. These data examined exposure by various EU population groups to all seven sweeteners of interest.…”
Section: Methodology and Trends In Intakementioning
confidence: 99%
“…These data examined exposure by various EU population groups to all seven sweeteners of interest. Most of the scientific opinions published by the EFSA examined intake in response to requests for extension of use for specific sweeteners considering the total diet [73,74] or in foods for special medical purposes (FSMPs) [75,76]. Acesulfame-K and aspartame have been the most frequently evaluated sweeteners in Europe, with intakes estimated for both sweeteners in 16 different peer-reviewed publications and in one EFSA scientific opinion.…”
Section: Methodology and Trends In Intakementioning
confidence: 99%
See 2 more Smart Citations
“…The authors Higginbotham et al (1983) also denote that thaumatin does not cause any hazardous effect when used as a flavor modifier or partial sweetener within a specific level of consumption. The safety of this protein was evaluated by SCF and JECFA who concluded that thaumatin can be considered as an acceptable ingredient for use (European Food Safety Authority (EFSA) Panel on Food Additives and Nutrient Sources Added to Food, 2015). This sweet protein is approved within the European Union since 1984 (E957) under Annex II of Regulation (EC) No.…”
Section: Thaumatinmentioning
confidence: 99%